FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENJUALAN SAMBAL BAWANG “BEBEK & AYAM SPESIAL BUMBU IRENG– DI DESA PLINTAHAN -“ KECAMATAN PANDAAN - Sibyan, Ahmad; Kurniastuti, Tri (Universitas Islam Balitar, 2016)
Agriculture product processing especially chilli already growth up in line needs of consumers consumption as sauce. The purpose of this research was to determine the volume and value sales trends and the factors that influence on it by the object of the research at Union Sauce “Bebek & Ayam Spesial Bumbu Ireng– Desa Plintahan -“ Kecamatan Pandaan. The research methods are used literature study and field research on this object business, with the result that the trend volume and value sales showed a positive trend over the last 3 years and significantly affected by the independence variable (price, price of others product, promotion dan distribution). As evident by F count 303, 276 with linear regeression calculations of all variables that most influence volume and value of sales are distribution (12,063 and 9,355), Price of product (10,238 and 7,554) and Other Product Price (-10,510 and -7,817)